PENINGKATKAN BERPROSES SISWA DALAM BELAJAR IPS DENGAN TEKNIK “OVAL – ET” - Sad Diana (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2013)
This study aims to: 1) increase the involvement of students in learning activities proceed on Population Problems materials and Abatement Efforts through learning techniques OVAL-ET, 2) improving student learning outcomes in social studies learning through techniques OVAL-ET, and 3 ) determine students responses to the application of learning to OVAL-ET techniques in social studies for VIII A grade students of SMP Negeri 2 Rawalo in the first semester in the Academic Year 2010/2011. Questionnaires and interviews were used to collect data about their interests, and the assessment for learning social studies, while the observations are used to collect data about student involvement in various aktvitas proceed to learn both in the classroom and outside the classroom, and learning logs are used to determine students responses to the application of engineering OVAL-ET in teaching social studies. Based on the data from this study concluded Technique